Estimation of Prospective Benefit Reserve Based on Gross Premium Valuation Method using Indonesian Mortality Table IV and De-Moivre Assumptions - Anastasya Prionggo , Echa; Pratama, Mohammad Nabil; NL , Amandaputri; Indrayatna, Fajar (Enthusiastic : International Journal of Applied Statistics and Data Science, 2022)
According to regulations, life insurance companies must meet several requirements related to the company's financial health, one of which is a technical reserve. Technical or premium reserves are funds that the insurance companies must prepare. These funds will cover financial losses experienced by someone who applies for the claim. Thus, the author will use the Gross Premium Valuation (GPV) method in this research. Premium reserves can be determined using two approaches: retrospective and prospective reserves. In this research, the author will determine the prospective reserves with GPV for single decrement insurance and single life n-year continuous term life. The distribution of deaths used in determining the probability of death is the Indonesian life table IV and the de-Moivre assumption with parameter (ɷ=111). Different assumptions for the death probability distribution will result in different premium reserve values, so we can see a difference in premium reserves resulting from the two death probability distributions. This research uses data from male policyholders aged 40 years who followed continuous term life insurance for 20 years. Benefits will be paid right at the time of death, with a discrete method of premium payments made at the beginning of each year for 10 years.